Bede : Commentary on revelation - Beda Venerabilis, asi 672-735 (Translated texts for historians ;, 2013)
The Commentary on Revelation is Bede's first venture into Biblical exegesis - an ambitious choice for a young monastic scholar in a newly Christianized land. Its subject matter – the climax of the great story of creation and redemption, of history and of time itself – adds to the Commentary's intrinsic importance, for these themes lie at the heart of Bede's concerns and of his achievement as a historian, exegete, scholar, and preacher. But Bede was also a man of his age. When he penned the Commentary around 703, speculation and anxiety about the end of the world was in the air. According to conventional chronology, almost 6000 years had passed since creation. If for God 'one day... is as a thousand years, and a thousand years as one day' (2 Peter 3:8), the world was destined to last six millennia, corresponding to the six days of creation. The end, then, was close. Bede vigorously opposed the temptation to calculate the time of the end. The Commentary argues that Revelation is not a literal prophecy, but a symbolic reflection on the perennial struggle of the Church in this world. At the same time, the young Bede is starting to shape his own account of how the end-times would unfold. This translation, prefaced by a substantial Introduction, will be of interest to students of medieval religious and cultural history, of Anglo-Saxon England, and of the history of Biblical exegesis in the Middle Ages.